Thematic and methodological foundations of Alfred Hitchcock's artistic vision - Drumin, William A. (Studies in history and criticism of film, 2004)
Although Alfred Hitchcock has been dead for over 24 years, his films still command widespread public interest and appeal. As true classics, they exhibit a persistent power to engage and enchant that transcends the limitations of time and culture. This work explores on a basic level the sources of the dramatic power of Hitchcock's films. An introductory chapter gives a brief outline of Hitchcock's career and the primary features of his approach to filmmaking. A concluding chapter surveys the elements of Hitchcock's humanistic vision. Two appendices illustrate Hitchcock's power to reveal inner c.